2016
DOI: 10.1002/pmic.201500423
|View full text |Cite
|
Sign up to set email alerts
|

Human aqueous humor proteome in cataract, glaucoma, and pseudoexfoliation syndrome

Abstract: Twenty-nine human aqueous humor samples from patients with eye diseases such as cataract and glaucoma with and without pseudoexfoliation syndrome were characterized by LC-high resolution MS analysis. In total, 269 protein groups were identified with 1% false discovery rate including 32 groups that were not reported previously for this biological fluid. Since the samples were analyzed individually, but not pooled, 36 proteins were identified in all samples, comprising the constitutive proteome of the fluid. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
59
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 53 publications
3
59
0
1
Order By: Relevance
“…However, during the method development not only the number of metabolites detected but also the reproducibility of measured intensities of metabolic features and the number of features in the blank extractions were taken into account. AH is to some extent similar to blood plasma as it contains plasma proteins and metabolites which are filtered to AH through fenestrated capillaries of the ciliary body stroma via the iris root [14]. Although the total concentration of proteins in AH seems to be low (five times lower than in blood plasma [14]), protein depletion in AH sample was performed before metabolite analysis.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, during the method development not only the number of metabolites detected but also the reproducibility of measured intensities of metabolic features and the number of features in the blank extractions were taken into account. AH is to some extent similar to blood plasma as it contains plasma proteins and metabolites which are filtered to AH through fenestrated capillaries of the ciliary body stroma via the iris root [14]. Although the total concentration of proteins in AH seems to be low (five times lower than in blood plasma [14]), protein depletion in AH sample was performed before metabolite analysis.…”
Section: Resultsmentioning
confidence: 99%
“…AH is to some extent similar to blood plasma as it contains plasma proteins and metabolites which are filtered to AH through fenestrated capillaries of the ciliary body stroma via the iris root [14]. Although the total concentration of proteins in AH seems to be low (five times lower than in blood plasma [14]), protein depletion in AH sample was performed before metabolite analysis. This step was used to eliminate potential enzymatic reactions between proteins and metabolites.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, as some patients (two in the glaucoma, one in the control group) received cholesterol-lowering drugs, an influence of systemic medication on this finding cannot completely ruled out. Interestingly, Kliuchnikova and coworkers also identified cholesterol metabolism to be influenced during glaucoma, with apolipoprotein D down-regulated during pseudoexfoliation syndrome [6]. Furthermore, GO analysis revealed that significantly enriched proteins are related to the acute phase response with Scavenger receptor cysteine-rich type 1 protein M130, Alpha-2-antiplasmin, Alpha-1-antichymotrypsin, Inter-alpha-trypsin inhibitor heavy chain H4, Alpha-2-HS-glycoprotein, and Prothrombin upregulated in glaucomatous aqueous humor.…”
Section: Resultsmentioning
confidence: 99%